Synthesis and thermal decomposition of a pyridylene-bridged bis-beta-diketiminate magnesium hydride cluster - Harder, Sjoerd; Spielmann, Jan; Intemann, Julia (Dalton Transactions, 2014)
Reaction of PYR-(MgnBu)(2), in which PYR is 2,6-[(DIPP)NC(Me)CHC(Me)N-]2-pyridine and DIPP is 2,6-iPr(2)-phenyl, with (DIPP)NH2BH3 gave PYR-[MgNH(DIPP)BH3](2) (56%) which was characterized by crystal structure determination. Addition of THF resulted in beta-H elimination and formation of PYR-[MgNH(DIPP)-BH3](MgH)center dot THF (57%), likewise characterized by crystal structure determination. Conversion of the second amidoborane anion in H- could not be achieved. Reaction of PYR-(MgnBu)(2) with PhSiH3 gave PYR(MgH)(2), which crystallized as a dimer. The structure of [PYR-(MgH)(2)](2) shows an 8-membered ring of Mg2+ and H- ions. Thermal decomposition at 130 degrees C releases one equivalent of H-2, i.e. 50% of the expected value. Nucleophilic attack at the para-position and reduction of the pyridylene bridge might explain reduced H-2 release.